The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1021/acsbiomedchemau.2c00046
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity and Kinetics of RNA Hydrolysis by SARS-CoV-2 NSP10/14 Exonuclease

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the virus that causes COVID-19, continues to evolve resistance to vaccines and existing antiviral therapies at an alarming rate, increasing the need for new direct-acting antiviral drugs. Despite significant advances in our fundamental understanding of the kinetics and mechanism of viral RNA replication, there are still open questions regarding how the proofreading exonuclease (NSP10/NSP14 complex) contributes to replication fidelity and resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…1 Furthermore, remdesivir's efficacy against various variants, including sublineages BQ.1.1 and XBB, has sustained its usage for over two-anda-half years. [2][3][4] Additionally, a meta-analysis revealed an exceptionally low pooled COVID-19 mortality rate associated with its use, and another study demonstrated its potential to reduce mortality among COVID-19 patients requiring supplemental oxygen therapy. 5,6 Despite its clinical benefits, the administration of remdesivir has been associated with the development of hyperglycemia, a condition characterized by elevated blood glucose levels both during and after therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Furthermore, remdesivir's efficacy against various variants, including sublineages BQ.1.1 and XBB, has sustained its usage for over two-anda-half years. [2][3][4] Additionally, a meta-analysis revealed an exceptionally low pooled COVID-19 mortality rate associated with its use, and another study demonstrated its potential to reduce mortality among COVID-19 patients requiring supplemental oxygen therapy. 5,6 Despite its clinical benefits, the administration of remdesivir has been associated with the development of hyperglycemia, a condition characterized by elevated blood glucose levels both during and after therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Furthermore, remdesivir's efficacy against various variants, including sublineages BQ.1.1 and XBB, has sustained its usage for over two‐and‐a‐half years. 2 , 3 , 4 Additionally, a meta‐analysis revealed an exceptionally low pooled COVID‐19 mortality rate associated with its use, and another study demonstrated its potential to reduce mortality among COVID‐19 patients requiring supplemental oxygen therapy. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%